USING WRITING FRAMES TO IMPROVE DESCRIPTIVE TEXT WRITING SKILL OF THE TENTH GRADERS OF MAN KOTA MAGELANG IN THE SCHOOL YEAR 2018/2019 - Amalia nisaul haqi (Journal of Research on Applied Linguistics, Language, and Language Teaching, 2020)
Writing is about sharing ideas in the form of written text. The students need detail understanding about language components, for example grammar, vocabulary, punctuation and spelling.There are two main objectives of this research. First, is to know the increase of the learning motivation in descriptive text writing skill. Second, is to measure the improvement in descriptive text writing skill of the tenth graders of MAN 1 Kota Magelang in the school year 2018/2019 who are taught using Writing Frames technique. The subject of this research is X Religion 3 class of MAN Kota Magelang. The writer conducted a classroom action research that was divided into Pre-Cycle, Cycle I, and Cycle II. In the collecting data, the writer used non-test (observation, questionnaire, and documentation) and test technique.As the results, the mean of the students’ score in Pre-cycle were 68.00, in Cycle I it was72.73, while  in Cycle II it was 78.11. The improvement from Pre-Cycle to Cycle II was10.11points. As suggest, both for the teacher and the students, can use Writing Frames technique as an alternative way in teaching and learning process of writing.